Back to nature or forward planning?: Regional policy, cultural perceptions and coastal tourism development in Hyōgo prefecture, Japan - Crowe-Delaney, Lesley Joy (Curtin University, 2015)
This thesis argues that tourism and coastal development in two locations in Hyogo Prefecture, Japan have resulted in inequitable outcomes as a result of historical factors and inappropriate tourism strategies. Late twentieth century policies have perpetuated a rural/urban dichotomy with metropolitan tourism attraction competing with enterprises based on nature-concepts of coastal fishing, gourmet tourism and the rural idyll. This thesis concludes that tourism requires its own portfolio of better informed strategies, and that research on coastal development in Japan would benefit from interdisciplinary collaboration.